The effect of standard dose multivitamin supplementation on disease progression in HIV infected adults initiating HAART: a randomized double blind placebo-controlled trial in Uganda - Guwatudde, David; Wang, Molin; Ezeamama, Amara E.; Bagenda, Danstan; Kyeyune, Rachel; Wamani, Henry; Manabe, Yukari C.; Fawzi, Wafaie W. (BMC infectious diseases, 2015)
Efficacy trials investigating the effect of multivitamin (MV) supplementations among patients on Highly Active Antiretroviral Therapy (HAART) have so far been inconclusive. We conducted a randomized, double blind, placebo controlled trial to determine the effect of one recommended daily allowance (RDA) of MV supplementation on disease progression in patients initiating HAART. Methods: Eligible subjects were randomized to receive placebo or MV supplementation including vitamins Bcomplex, C and E. Participants were followed for up to 18 months. Primary endpoints were: change in CD4 cell count, weight and quality of life (QoL). Secondary endpoints were: i) development of a new or recurrent HIV disease progression event, including all-cause mortality; ii) switching from first- to second-line antiretroviral therapy (ART); and iii) occurrence of an adverse event. Intent-to-treat analysis, using linear regression mixed effects models were used to compare changes over time in the primary endpoints between the study arms. Kaplan-Meier time-toevent analysis and the log-rank test was used to compare HIV disease progression events and all-cause mortality. Results: Four hundred participants were randomized, 200 onto MV and 200 onto placebo. By month 18, the average change in CD4 cell count in the MV arm was 141 cells/uL compared to 147 cells/uL in the placebo arm, a mean difference of −6 · 17 [95 % CI −29 · 3, 16 · 9]. The average change in weight in the MV arm was 3 · 9 kg compared to 3 · 3 kg in the placebo arm, a mean difference of 0 · 54 [95 % CI −0 · 40, 1 · 48]; whereas average change in QoL scores in the MV arm was 6 · 8 compared to 8 · 8 in the placebo arm, a mean difference of −2.16 [95 % CI −4 · 59,0 · 27]. No significant differences were observed in these primary endpoints, or in occurrence of adverse events between the trial arms. Conclusions: One RDA of MV supplementation was safe but did not have an effect on indicators of disease progression among HIV infected adults initiating HAART.
Keywords: Dose multivitamin supplementation; Disease progression; HIV infected adults; HAART; Blind placebo-controlled trial; Uganda